The Obstacles Detector with Tahani Fuzzy Logic as The Tool for Blind People - ., Abdurrasyid; Arianto, Rakhmat; Indrianto, Indrianto; Nugroho, Bramantyo Adi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 2 August 2018, 2018)
Indonesian Blind Union said that the number of blind people in Indonesia reached 3.75 million and 40% in school-age children, and this number will continue to increase each year. Blind people will need the tool to help their day to day activities. The research that has been developed still have flaws, where as they do not provide the sound of information to the people with visual impair ment about the obstacle, included no scientific method used in the research , especially about how the appliance works. T his research does not only provide ‘ beep ’ sound when obstacles are detected , but also provides audio information through a headset to the blind people . T here are three obstacles detected , they are hole s , bumps, and wall s , and it can help the blind people to decide whether to dodge or to step high. To support the audio output and the design processing speed of the appliance, this research use s Raspberry Pi 3 mini PC , three ultrasonic sensors that are used to detect obstruction objects upright, hole and bump , and to initialize the initial values before it detects the obstruction. Tahani fuzzy logic method used t o different obstacles such as the bump s, flat surfaces, or holes so the blind people feel much safer while walking .